2000
DOI: 10.1292/jvms.62.1125
|View full text |Cite
|
Sign up to set email alerts
|

Porcine Circovirus Induces B Lymphocyte Depletion in Pigs with Wasting Disease Syndrome.

Abstract: To disclose the mechanism of cellular injury following porcine circovirus (PCV) infection, 12 pigs were examined by the terminal deoxynucleotidyl transferase-mediated dUTP-nick end labeling (TUNEL) method and immunohistochemistry. Histologically, the lymphoid tissues were characterized by marked apoptosis of lymphocytes, lymphocyte depletion, and macrophages and giant cells containing numerous inclusion bodies with or without apoptotic bodies. Immunohistochemically, there were many lysozyme-positive macrophage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
62
3
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(73 citation statements)
references
References 18 publications
6
62
3
2
Order By: Relevance
“…It was suggested that this decrease could be due to the apoptotic effect that PCV2 infection might have on B cells (23). The results of our analysis of IgM ϩ cell levels showed two different clusters of animals within the PCV2-positive group: pigs with proportions of IgM ϩ cells of Ͻ5% and pigs with proportions of Ͼ5%.…”
Section: Discussionmentioning
confidence: 67%
See 4 more Smart Citations
“…It was suggested that this decrease could be due to the apoptotic effect that PCV2 infection might have on B cells (23). The results of our analysis of IgM ϩ cell levels showed two different clusters of animals within the PCV2-positive group: pigs with proportions of IgM ϩ cells of Ͻ5% and pigs with proportions of Ͼ5%.…”
Section: Discussionmentioning
confidence: 67%
“…Some of these changes have been described in other reports (19,20,23), in which the reduction of T cells was associated with a decrease or shift in the CD4 ϩ cell subset (19,20). In those reports, only PCV2-positive or healthy pigs were examined.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations